The right to live in health : medical politics in postindependence Havana - Rodríguez, Daniel A., 1976- (Envisioning Cuba., 2020)
"Rodríguez describes how medicine and new public health projects infused republican Cuba's statecraft, powerfully shaping the lives of Havana's residents. He underscores how various stakeholders, including women and people of color, demanded robust government investment in quality medical care for all Cubans, a central national value that continues today. On a broader level, Rodríguez proposes that Latin America, at least as much as the United States and Europe, was an engine for the articulation of citizens' rights, including the right to health care, in the twentieth century"--